Women Trespassing - Oktay, Elif Miral (Feminist Asylum: A Journal of Critical Interventions, 2023)
This photo was taken within the scope of the project titled Squatter Women's Right to the City: Urbanity, Participation, Experience carried out by Leyla Bektaş Ata and supported by the Raoul Wallenberg Institute in 2019.